Relationship between the Multiannual Investment Programming and the closing of social and economic gaps - Segura-Espinoza, Elsa E. (2024)
Objective. Establish to what extent the Multiannual Investment Programming is related to the closing of social and economic gaps in the district of Tomayquichua, 2022-2023. Materials and methods. The research was characterized by being of type transectional, with a correlational explanatory level and a non-experimental design. The theory of the Invierte.pe directive was employed, where information was found regarding the Multiannual Investment Programming and social and economic gaps. For data collection, a structured questionnaire was applied to the mayor, councilors, and person in charge of the Multiannual Investment Programming office of the District Municipality of Tomayquichua. With base to it, the Pearson correlation coefficients were estimated. Results. It was found evidence of a positive relationship between the Multiannual Investment Programming and the closing of social and economic gaps (R = 0.750). Conclusions. A study was carried out among the councilors, the mayor, and the head of the OPMI of the Municipality of Tomayquichua and it was found that with a probability of 95.0 % the following multiannual investment plan will be maintained to reduce social and economic inequality in the Tomayquichua district, 2022-2023.